The college solution : a guide for everyone looking for the right school at the right price - O'Shaughnessy, Lynn, 1955- (FT Press, 2008)
"The College Solution helps readers look beyond over-hyped admission rankings to discover schools that offer a quality education at affordable prices. Taking the guesswork out of saving and finding money for college, this is a practical and insightful must-have guide for every parent!"--Jaye J. Fenderson, Seventeen's College Columnist and Author, Seventeen's Guide to Getting into College "This book is a must read in an era of rising tuition and falling admission rates. O'Shaughnessy offers good advice with blessed clarity and brevity." --Jay Mathews, Washington Post Education Writer and Columnist "I would recommend any parent of a college-bound student read The College Solution ." --Kal Chany, Author, The Princeton Review's Paying for College Without Going Broke " The College Solution goes beyond other guidebooks in providing an abundance of information about how to afford college, in addition to how to approach the selection process by putting the student first." --Martha "Marty" O'Connell, Executive Director, Colleges That Change Lives "Lynn O'Shaughnessy always focuses on what's in the consumer's best interest, telling families how to save money and avoid making costly mistakes." --Mark Kantrowitz, Publisher, FinAid.org and Author, FastWeb College Gold "An antidote to the hype and hysteria about getting in and paying for college! O'Shaughnessy has produced an excellent overview that demystifies the college planning process for students and families." --Barmak Nassirian, American Association of Collegiate Registrars and Admissions Officers For millions of families, the college planning experience has become extremely stressful. And, unless your child is an elite student in the academic top 1%, most books on the subject won't help you. Now, however, there's a college guide for everyone . In The College Solution, top personal finance journalist Lynn O'Shaughnessy presents an easy-to-use roadmap to finding the right college program (not just the most hyped) and dramatically reducing the cost of college, too. Forget the rankings! Discover what really matters: the quality and value of the programs your child wants and deserves. O'Shaughnessy uncovers "industry secrets" on how colleges actually parcel out financial aid--and how even "average" students can maximize their share. Learn how to send your kids to expensive private schools for virtually the cost of an in-state public college ... and how promising students can pay significantly less than the ...